2012
DOI: 10.1590/s0102-86502012000900011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anatomical and functional changes esophageal stump of patients with advanced megaesophagus submitted to subtotal laparoscopic esophagectomy

Abstract: PURPOSE:Evaluate anatomical and functional changes of the esophageal stump and gastric fundus of patients with advanced megaesophagus, submitted to laparoscopic subtotal esophagectomy. METHODS: Twenty patients with advanced megaesophagus, previously submitted to a videolaparoscopic subtotal esophagectomy , were evaluated. Were conducted: radiological evaluation of the stump esophagus with transposed stomach, electromanometric, endoscopic examination and histopathology of the esophageal stump and gastric fundus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Therefore, surgical procedures in which the mucosa is resected would be more suited to prevent the development of carcinomas. However, previous esophagectomy studies have reported a high incidence of gastroduodenal reflux, resulting in esophagitis, development of Barrett epithelium [19] and, subsequently, carcinoma of the esophageal stump [20], in addition to the relatively higher rate of morbidity and mortality associated with resection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surgical procedures in which the mucosa is resected would be more suited to prevent the development of carcinomas. However, previous esophagectomy studies have reported a high incidence of gastroduodenal reflux, resulting in esophagitis, development of Barrett epithelium [19] and, subsequently, carcinoma of the esophageal stump [20], in addition to the relatively higher rate of morbidity and mortality associated with resection.…”
Section: Discussionmentioning
confidence: 99%